2011
DOI: 10.1021/bm201599j
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cellulose Nanocrystals Amphiphilic Properties to Stabilize Oil/Water Interface

Abstract: Neutral cellulose nanocrystals dispersed in water were shown in a previous work to stabilize oil/water interfaces and produce Pickering emulsions with outstanding stability, whereas sulfated nanocrystals obtained from cotton did not show interfacial properties. To develop a better understanding of the stabilization mechanism, amphiphilic properties of the nanocrystals were modulated by tuning the surface charge density to investigate emulsifying capability on two sources of cellulose: cotton linters (CCN) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
480
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 549 publications
(508 citation statements)
references
References 40 publications
27
480
0
1
Order By: Relevance
“…at molecular contact 3.7 nm. Such a surface density is in agreement with values found in the literature (Kalashnikova et al 2012 be found, as experimentally determined here. The long-ranged electrostatic repulsion increased in the following order 50 mM NaCl \ 5 mM CaCl 2 \ 0.2 mM AlCl 3 , and for the short-ranged electrostatic repulsion, we found the opposite behavior.…”
Section: Monte Carlo Simulationssupporting
confidence: 93%
“…at molecular contact 3.7 nm. Such a surface density is in agreement with values found in the literature (Kalashnikova et al 2012 be found, as experimentally determined here. The long-ranged electrostatic repulsion increased in the following order 50 mM NaCl \ 5 mM CaCl 2 \ 0.2 mM AlCl 3 , and for the short-ranged electrostatic repulsion, we found the opposite behavior.…”
Section: Monte Carlo Simulationssupporting
confidence: 93%
“…Besides, the less charged holoCNCs could also shift toward stronger inter holoCNC association and away from hydrophilic interaction with water to stabilize the O/W interfaces, as highly charged CNCs have been known to reversibly desorb from the oil/ water interface, except when the negative charge groups are removed by desulfation or screened by increasing ionic strength. 55,56 The hydrodynamic diameters of the emulsion droplets in holoCNCs stabilized emulsions were 1.2−1.6 μm, double in sizes (0.6−0.8 μm) of those in CNC stabilized emulsions (Figure 4b). The significantly larger hydrodynamic diameters of emulsion droplets stabilized with holoCNCs are further proof to their greater hydrophobicity to stabilize more oil.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…CNCs have recently been used as emulsion stabilizers by taking advantage of their selfassembling ability at the oil-water interface, similar to particle-stabilized Pickering systems [16,17]. They thus lead to the formation of ultrastable and monodispersed oil-in-water emulsions.…”
Section: Introductionmentioning
confidence: 99%